Idiopathic Intracranial Hypertension and Anemia: A Matched Case–Control Study. Issue 2 (June 2020) - Lin, Weijie Violet; Berry, Shauna; Nakawah, Mohammad Obadah; Sadaka, Ama; Lee, Andrew G.
Abstract : Background: An association between idiopathic intracranial hypertension (IIH) and anemia has been speculated from previous case reports and case series. Retrospective studies to date have not used matched case controls to compare standardized complete blood count (CBC) values for the presence of anemia. Methods: At our tertiary care facility, 50 patients with IIH were matched with 50 case–control patients to compare CBC values from laboratory affiliates with standardized ranges. Results: No significant difference was found for any CBC parameters for IIH vs control patients. For female IIH and control patients as well as male IIH patients, values for red blood cell count, hemoglobin (HGB), and hematocrit (HCT) tended to trend on the lower end of "normal" range, whereas this was not seen in male control patients. Conclusions: In this retrospective, matched case–control study, no significant association was found between IIH and anemia when comparing standardized CBC values. In accordance with previous studies, the prevalence of anemia may be relatively higher in the IIH population due to a prominent demographic overlap of females of child-bearing age.